Penguatan Asas Kebebasan Berkontrak Untuk Kepentingan Umum Dalam Layanan Pinjaman Online Dengan Menggunakan Pendekatan Rule of Law - Harniwati, Harniwati; Fauzi, Engrina; Fajar, Abdul Malik (Nagari Law Review, 2023)
This article analyzes the setting of very high interest rates on information technology-based lending and borrowing services by the Indonesian Funding Fintech Association (AFPI). AFPI was given self-regulating authority by the OJK (Financial Services Authority) to determine loan interest rates which caused disproportionate positions between borrowers and lenders. This research aims to answer problems in terms of the substance of fintech peer to peer lending regulations in Indonesia, so a comprehensive analysis is needed from the perspective of statutory regulations and conceptually so that legal protection can be achieved for the public, especially borrowers. The results of this research show that the unequal position of the parties in fintech agreements is due to a lack of understanding of the principle of complete freedom of contract. The application of the principle of freedom of contract in fintech can be said to be not optimal and still applies artificially due to the urgent interests of borrowers who are in a weak position where urgent needs are forced to agree to agreements with high interest rates. It is necessary to limit the principle of freedom of contract because it has an impact on injustice and in the public interest it is necessary to break through public law into civil law. Apart from that, it is necessary to strengthen the Pancasila economic system again because it is in accordance with the identity of the Indonesian nation. Apart from that, the law must be a determinant of the economy, not as an instrument to support the economic system, thus causing the economy to be more determinant over the law.